Issues Of Forming Inclusive Competence In The Professional Training Of Future Teachers - Sharopova Umida Raxmatovna; Isakbayeva Mahina Murodjon qizi; Bakhriddinova Sabrina Fakhriddin qizi; Zaribova Dilnur Nuraddin qizi (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This scientific article discusses the issues of forming inclusive competence in future teachers in the context of introducing inclusive education in the modern education system. The study analyzes the philosophical, pedagogical and social foundations of inclusive education and shows effective ways to organize the educational process taking into account the special educational needs of children with disabilities. Also, the possibilities of forming inclusive competence for students studying in the areas of physical education, social pedagogy and informatics in the information and educational environment of a higher educational institution are substantiated. The article pays special attention to the issues of using information and communication technologies, developing adapted educational programs and creating a barrier-free educational environment. The results of the study are of practical importance for improving the system of training pedagogical personnel in the development of inclusive education.